2002
DOI: 10.1021/jp026747o
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy Studies on the Interaction of Imidazole with a Silver Electrode in Acetonitrile Solution

Abstract: Surface-enhanced Raman scattering (SERS) spectrum of imidazole adsorbed at a silver electrode in nonaqueous acetonitrile solution has been investigated as a function of applied potential. The electrolyte is 0.1 M LiClO4. Results show that imidazole adsorbs on silver as a neutral molecule via the pyridine nitrogen atom. Coadsorption of perchlorate anion with imidazole, possibly by forming intermolecular hydrogen bonding, is also suggested by the enhancement of the ClO4 - band at 933 cm-1. An edge-on orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 45 publications
7
46
0
3
Order By: Relevance
“…A m(CÀ ÀS) band corresponding to the À À(H 2 )CÀ ÀSÀ À group was expected to appear in the 640-680 cm 21 ) gave rise to several well-defined vibrational bands in the vibrational spectra of NMB and PG-L (Table II). [51][52][53] None of the ]phyllolitorin spectra because these peptides do not contain Phe 13 and His 12 residues, respectively. On the other hand, the strong bands due to the aromatic ring system of Trp 8 (W18, W17, W7, and W3) were observed in all the spectra.…”
Section: Resultsmentioning
confidence: 99%
“…A m(CÀ ÀS) band corresponding to the À À(H 2 )CÀ ÀSÀ À group was expected to appear in the 640-680 cm 21 ) gave rise to several well-defined vibrational bands in the vibrational spectra of NMB and PG-L (Table II). [51][52][53] None of the ]phyllolitorin spectra because these peptides do not contain Phe 13 and His 12 residues, respectively. On the other hand, the strong bands due to the aromatic ring system of Trp 8 (W18, W17, W7, and W3) were observed in all the spectra.…”
Section: Resultsmentioning
confidence: 99%
“…From the fact that SERS became effective after laser illumination, it was proposed that the photographitization of organic compounds on the metal surface, rather than the metal itself, was responsible for the SERS phenomenon. 40,41 Cao et al 42 also reported broad background features between 1300 and 1600 cm 1 and have attributed them to the presence of surface carbon impurities.…”
Section: Ir and Raman Spectramentioning
confidence: 97%
“…These features just exhibit an 'edge-on' adsorption mode of pyridine ring. [38] However, we exclude the direct adsorption of PN on the roughened substrate for the interaction between Sn(II) and Au is stronger than that between PN and Au. That is why PN is not decomposed by the giant EMF in the absence of the 'first-layer' effect.…”
Section: High-quality Sers Spectra Of Pn In the Presence Of Snclmentioning
confidence: 99%